Innate and Adaptive Immunity Imbalance With Severe COVID-19 Pneumonia in Children and Adults - Shokati Eshkiki, Zahra; Shahriari, Arman; Seyedtabib, Maryam; Torabizadeh, Mehdi; Assarehzadegan, Mohammad Ali; Nashibi, Roohangize; Khosravi, Maryam; Neisi, Niloofar; Mard, Seyed Ali; Shayesteh, Ali Akbar (Frontiers in Pediatrics, 2021)
Introduction: Little is known about the laboratory, radiological characteristics, and clinical significance of peripheral immune alterations in patients with coronavirus disease 2019 (COVID-19). This study aims to clarify these aspects in children and adults with COVID-19. Methods: In this consecutive pilot study, COVID-19 patients with the confirmed pneumonia and real-time RT-PCR; were recruited prospectively in June 2020. The clinical, chest CT features, laboratory features such as lymphocyte subpopulations were analyzed for each individual. Results: Forty confirmed COIVID-19 patients, 11 severe children, 12 severe adults, and 17 critical adult patients, besides 20 healthy pediatrics and 14 healthy adults as controls, were enrolled prospectively. Adult patients, especially critical ones, had a much higher prevalence of laboratory and chest CT abnormalities. Data regarding immune cell subsets in Children patients, compared matched-controls, had higher CD3+ CD8+ T cells (P =0.004), and lower CD4+/CD8+ ratio (P = 0.042), while adult patients, compared with matched controls, had lower CD14+ monocytes (P = 0.032). Adult patients were also, categorized as experiencing critical or severe illness on admission and compared with severe patients, had lower total lymphocytes (p ˂ 0.047), CD3+ T-lymphocytes (p ˂ 0.002) and CD3+ CD8+ T cells (P = 0.001) and on the other hand, had higher CD3+ CD4+ T cells (P = 0.012), and CD4+/CD8+ ratio (P = 0.003). Non survived adults, compared with survived patients, had significantly lower CD3+ T-lymphocyte (P = 0.005). Conclusion: Unlike adult patients, who compared with matched controls, had more comorbidities, higher frequency of severe clinical symptoms, laboratory abnormalities, and immune cells alteration; clinical manifestations of COVID-19 in children (compared with matched controls) were quite mild, and fewer clinical complications were seen either, perhaps because of a milder inflammatory response following their peripheral innate and adaptive immune cell alteration pattern.